Problem-Based Learning (PBL) as a methodology to strengthen mathematical skills —problem solving— in Basic Education (2024)
Introduction: Problem solving is considered a crosscutting strategy that gives meaning to the teachinglearning process and creates new environments that promote the development of mathematical skills. Objective: To analyze the influence of PBL in the development of mathematical problem-solving skills in middle school students. Methodology: A quantitative study with a quasi-experimental design involving pre-test and post-test, carried out in three phases: characterization of the problem-solving skills, experimentation based on implementation of the PBL methodology, explanation of the assessment of strengths and difficulties in acquiring the skills. Results: It is shown that the implementation of the PBL methodology manages to improve the skill performance levels by optimizing the processes of phase 1 (understanding of the problem) and phase 3 (execution of the plan). Conclusions: Mathematical problem-solving skills are enhanced through processes that combine complementary cognitive and procedural activities related to the particular context and the formal structures that comprise mathematical knowledge.